Quantitative Mineral Analysis of Ordinary Chondrites and Primitive Achondrites Using Reflectance Spectroscopy. Issue 12 (26th December 2022) - Wang, PengYue; Cloutis, Edward; Zhang, QinWei; Wu, YunZhao
Abstract: Visible and near‐infrared spectroscopy is a widely used method to determine the mineral compositions of meteorites and asteroids. In this study, we first investigated the association of multiple spectral parameters with mineral compositions using published laboratory spectra and mineral analysis of ordinary chondrites and primitive achondrites. New models for deriving the abundances of mafic silicate minerals were determined. Second, the influence of different mineral compositions on the 1.25 μm region is discussed. Finally, a method to distinguish the ordinary chondrites from primitive achondrites is developed. Our results suggest that the 1.25–1 μm band depth ratio (BDR 1.25) and 1 μm band width (BW I) are mainly associated with mineral abundances and to a lesser extent, compositions. Olivine is the dominant mafic mineral phase that affects the 1.25 μm region in ordinary chondrites and primitive achondrites. The plot of the BDR 1.25 versus the BW I is a useful method for correctly distinguishing about 90% of the primitive achondrites from ordinary chondrites. It relies largely on differences in olivine abundance and olivine/pyroxene ratios and to a lesser extent, olivine composition. The quantitative mineral analysis in this study based on the correlation between the spectra and mineralogy of ordinary chondrites and primitive achondrites provides a chance for understanding the petrology and geochemistry of S‐type asteroids. This study can also distinguish the partially melted S‐type asteroids (parent body of primitive achondrites) from the unmelted S‐type asteroids (parent body of ordinary chondrites). Plain Language Summary: Ordinary chondrites and primitive achondrites are two different types of meteorites with similar mineralogy but different histories: ordinary chondrites have never been significantly heated, while primitive achondrites experienced temperatures high enough to partially melt them. Thus, they represent asteroids with very different thermal histories. Identifying them in the asteroid belt can give us insights into the early thermal history of the Solar System. We examined reflectance spectra of multiple meteorites from both groups and found that we can distinguish them on the basis of the presence or absence of an absorption feature in the 1.2 μm region. This also allows us to determine the abundances of the major mafic minerals (olivine and pyroxene). The method we derived for spectral analysis can be used to determine whether taxonomic S‐type asteroids are primitive (unheated) or have undergone some melting. Key Points: New spectral models to derive the abundances of mafic silicate minerals of ordinary chondrites and primitive achondrites were built If olivine is the dominant mineral phase, the 1.25 μm region in ordinary chondrites and primitive achondrites is controlled by its presence A method to distinguish the ordinary chondrites from primitive achondrites was developed